CDrift: An Algorithm to Correct Linear Drift From A Single High-Resolution STEM Image. (October 2020) - Bárcena-González, Guillermo; Guerrero-Lebrero, María de la Paz; Guerrero, Elisa; Yañez, Andres; Nuñez-Moraleda, Bernardo; Fernández-Reyes, Daniel; Real, Pedro; González, David; Galindo, Pedro L.
Abstract : Abstract: In this work, a new method to determine and correct the linear drift for any crystalline orientation in a single-column-resolved high-resolution scanning transmission electron microscopy (HR-STEM) image, which is based on angle measurements in the Fourier space, is presented. This proposal supposes a generalization and the improvement of a previous work that needs the presence of two symmetrical planes in the crystalline orientation to be applicable. Now, a mathematical derivation of the drift effect on two families of asymmetric planes in the reciprocal space is inferred. However, though it was not possible to find an analytical solution for all conditions, a simple formula was derived to calculate the drift effect that is exact for three specific rotation angles. Taking this into account, an iterative algorithm based on successive rotation/drift correction steps is devised to remove drift distortions in HR-STEM images. The procedure has been evaluated using a simulated micrograph of a monoclinic material in an orientation where all the reciprocal lattice vectors are different. The algorithm only needs four iterations to resolve a 15° drift angle in the image.